2004
DOI: 10.1002/ppp.506
|View full text |Cite
|
Sign up to set email alerts
|

Development of transverse ridges on rock glaciers: field measurements and laboratory experiments

Abstract: Very high-resolution photogrammetric and geodetic measurements about the deformation of transverse ridges on Murtèl, Muragl and Suvretta rock glaciers in the Swiss Alps are discussed. The ridges are advected downstreams with a speed that equals the overall speed of the creeping permafrost within the significance level of the applied techniques. Any process of ridge formation is, thus, overlain on the mass creep. In fact, measurements yield local speed maxima on top of the ridges that can be explained by differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 21 publications
7
68
0
1
Order By: Relevance
“…Analogue experiments that model rock glacier internal deformation using Xanthan gum, sand and gravel have shown that transverse ridges are more likely to develop when heterogeneous materials are present (Kääb and Weber, 2004). Materials with heterogeneous viscosity and density yielded strong folding, while homogeneous materials yielded either no or slight folding (Kääb and Weber, 2004). Other model-derived data indicate that shearing occurs in ice-rich layers, while debris-rich layers respond to comparable stresses via brittle deformation (Moore and others, 2010).…”
Section: Heterogeneity Of Ice/debris and Glaciotectonically Altered Smentioning
confidence: 95%
See 1 more Smart Citation
“…Analogue experiments that model rock glacier internal deformation using Xanthan gum, sand and gravel have shown that transverse ridges are more likely to develop when heterogeneous materials are present (Kääb and Weber, 2004). Materials with heterogeneous viscosity and density yielded strong folding, while homogeneous materials yielded either no or slight folding (Kääb and Weber, 2004). Other model-derived data indicate that shearing occurs in ice-rich layers, while debris-rich layers respond to comparable stresses via brittle deformation (Moore and others, 2010).…”
Section: Heterogeneity Of Ice/debris and Glaciotectonically Altered Smentioning
confidence: 95%
“…thrust faulting or buckling due to rheological heterogeneity) (White, 1971;Loewenherz and others, 1989;Arenson and others, 2002;Fukui and others, 2007). Some researchers invoke specific endogenous processes and suggest that transverse ridges are a surface expression of thrust shearing in localized high-strain zones (White, 1971;Barsch, 1996;Arenson and others, 2002;Kääb and Weber, 2004). Upslope-dipping subsurface structures have been detected in previous ground-penetrating radar (GPR) surveys (Berthling and others, 2000;Fukui and others 2008), and in a few cases have been individually linked to surface ridges (Shean and Marchant, 2010;Monnier and others 2011).…”
Section: Introductionmentioning
confidence: 99%
“…2). It is moving horizontally a few centimeters per year (Kääb and Weber, 2004). The ongoing movements have generated numerous flow lobes (Fig.…”
Section: Site Descriptionmentioning
confidence: 99%
“…the European Commission (EC)-funded Permafrost and Climate in Europe (PACE) project; Harris and others, 2003). It is now recognized that detailed knowledge of the internal structure of permafrost is required for the optimum design of hazard-mitigation measures and for the numerical modeling of the dynamic behavior of permafrost (Arenson andothers, 2002, Kääb andWeber, 2004). Diffusive electromagnetic, geoelectric, seismic and ground-penetrating radar (georadar) techniques have proven to be suitable tools for determining the internal structure of permafrost in many regions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance debris flows, or creep of frozen or viscous masses (Kääb and Weber, 2004). To such models close-range remote sensing techniques such as particle tracking, or laser and microwave sounders can be applied.…”
Section: Modelling Of Hazard Potentialsmentioning
confidence: 99%